Imagem da banca: análise empírica de determinantes e efeitos - Vilar, Emilio Távora (2007)
Submitted by Teresa Segurado (teresa.segurado@iscte.pt) on 2007-10-30T12:16:23Z No. of bitstreams: 1 Imagem da Banca.pdf: 2637768 bytes, checksum: 6c1361143f8399746af053a0b7dc68f1 (MD5)